MO297MONOCLONAL GAMMOPATHY OF RENAL SIGNIFICANCE: A REPORT OF CASES FROM FOUR PORTUGUESE CENTERS. (29th May 2021) - Tavares, Joana; Reis, Marina Sofia Rodrigues; Silva, Filipa; Ferreira, Hugo; Chuva, Teresa; Paiva, Ana; Gomes, Ana Marta; Moreira, Carla; Santos, Maria Teresa; Silva, Sandra; Costa, José Maximino
Abstract: Background and Aims: Monoclonal gammopathy of renal significance (MGRS) refers to any plasma cell or B cell clonal lymphoproliferation that has at least one kidney lesion related to the monoclonal immunoglobulin productions plus, the underlying clone is not responsible for tumour complications. Plus, does not meet any haematological criteria for specific treatment. Although considered a non-malignant or smouldering hematologic condition, its effects on the kidney are not benign since it frequently evolves to end-stage renal disease. There has been some reluctance in treating these patients but increasing evidence has shown that renal outcomes are closely associated with the haematological response to chemotherapy. We aimed to evaluate the incidence of MGRS in the North of Portugal and to assess patients' characteristics, treatment and follow-up. Method: We have, retrospectively, collected information of all patients with a biopsy proven MGRS diagnosis, from four Portuguese centers. Demographic, clinical, laboratorial data and treatment were analysed. Follow-up was made until dialysis start, death of until December 2020. Survival curves were analysed according to the treatment performed, the histological diagnosis, the type of chains, the estimated glomerular filtration rate (eGFR) and proteinuria at the time of diagnosis. Baseline characteristics were reported as mean ± standard deviation (SD) and median (min-max) for continuous variables or as number (percentage) for categorical variables. Survival curves were analysed using Kaplan–Meier method. Statistical calculations were performed using SPSS. Results: Our study included 36 patients, with a mean age of 69 ± 11 years old and 52, 8% were males. At baseline, the median value of serum creatinine (sCr) was 1, 2 (0, 4-6, 3) mg/dL, which represented a mean eGFR of 55, 4 ± 30, 4 ml/min/1, 73 m 2 according to the CKD-EPI formula. The nephrotic syndrome was the most common (72%) renal presentation. The median proteinuria value was 8, 0 (0, 5-28) g per day and the mean albumin value was 2, 7 ± 0, 8 g/dL. The mean value of monoclonal protein was 5, 5 ± 4, 8 g/L with 62, 5% of the patients having an abnormal serum free light chain ratio. Table 1 describes the type of gammopathy found, being the IgG/Kappa the most observed. The immunoglobulin light chain amyloidosis (AL amyloidosis) and the monoclonal immunoglobulin deposition disease (MIDD), mainly light chain deposition disease (LCDD) were the most frequent histological diagnosis (Table 2 ). Monoclonal gammopathy of undetermined significance (MGUS) was the most frequent haematological diagnosis (Table 3 ). Treatment was done in 75% of the cases and bortemozib-based regimens were the most used. Three patients (8, 3%) received a bone marrow auto transplant. Approximately 40% of the patients had complete haematological and renal response. Treatment regimens and haematological and renal responses are summarized in Table 4 and 5 . Survival curves (Figures 1–2 ) were significantly higher in younger patients (p=0, 039) and both renal and global survival were better (p=0, 023) in MIDD compared to AL amyloidosis. No statistically significant differences were detected when analysing according to treatment, type of chain, eGFR, proteinuria and serum albumin at admission. Conclusion: The incidence of MGRS is probably underestimated and its treatment is yet far to be universal. In our series, 25% of the patients weren't proposed to any treatment. MGRS approach requires a multidisciplinary team composed by Nephrologists, Pathologists, Onco-Haematologists and a Bone Marrow Transplantation department. Since not all hospitals meet these conditions, referral centers of greater expertise are required for a prompt diagnosis and to provide the most adequate treatment. We hope that in a near future more centres join this project and that this represents the first step towards the creation of a Portuguese group dedicated to the study and treatment of MGRS.